Persuasion Strategies Used by Medical Experts vs. Political Figures: A Study of Coronavirus-Related Media Discourse - Mohammad Mohtasham; Fatemeh Mahdavirad; Ali Akbar Jabbari; Golnar Mazdayasna (Journalism and Media)
Concentrating on different types of persuasion strategies used by medical experts and political figures, the present study aims to examine persuasion strategies in medical vs. political discourse. Four corpora of speeches and interviews of four different groups of politicians and health professionals related to COVID-19 were selected. Two corpora belonged to Iranian figures, and two corpora represented Western figures. Then, using a framework which encompasses textual and interpersonal markers, the persuasive properties of the four corpora were investigated. The results indicated that logical markers emerge as the most frequent elements in textual subcategories of the persuasive metadiscourse observed in all four corpora. Moreover, in the case of the interpersonal subcategories, it was found that although hedges have a key role in the persuasive qualities of the texts, certainty markers appear to be largely absent within this corpus, which could suggest that the speakers are reluctant to take a stance while discussing a divisive and new issue such as COVID-19. The results provide insights into how the public’s understanding of the situation can be shaped and shifted in times of crisis, using persuasive devices by public figures.